Criminal Law and Islamic Perspectives on The Death Penalty in Parental Murder Cases - Fahmi, Zul; Sangidun, Muhammad; Ramadhan, Achmad Faiq; Qowima, Muhammad Roihan (Walisongo Law Review (Walrev), 2025)
The death penalty for the murder of a child by a parent is subject to differing standards of justice and proportionality between positive law and Islamic law. This disparity requires in-depth study and analysis of judicial rationality and criminal proportionality. This study assesses the rationality of the judge’s considerations and the proportionality of the death penalty in Mandailing Natal District Court Decision No. 40/Pid.B/2025/PN Mdl (parricide murder) from the perspective of Islamic criminal law, with a focus on qishash and maqashid al-shariah. The method used is normative legal research with a doctrinal and judgment study approach; the analysis materials include a copy of the verdict, the Criminal Code, fiqh literature, and contemporary studies analyzed descriptively-qualitatively and comparatively. The results show that the panel formally assessed the fulfillment of the elements of premeditated murder so that the verdict led to the death penalty according to Article 340 of the Criminal Code. Textually, the elements of qishash were fulfilled and the victim's family did not grant forgiveness, but weaknesses in forensic and psychiatric evidence reduced factual certainty, which is an important prerequisite under Islamic criminal law before applying a commensurate punishment. Hukuman mati dalam kasus pembunuhan yang dilakukan anak terhadap orang tuanya memiliki standar keadilan dan proporsionalitas hukuman yang tidak sama antara hukum positif dan hukum Islam. Kesenjangan ini memerlukan kajian dan analisis mendalam tentang rasionalitas yudisial dan proporsionalitas pidana. Penelitian ini menilai rasionalitas pertimbangan hakim dan proporsionalitas pidana mati dalam Putusan PN Mandailing Natal No. 40/Pid.B/2025/PN Mdl (pembunuhan orang tua oleh anak) dari perspektif hukum pidana Islam, dengan fokus pada qishash dan maqashid al-shariah. Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan doktrinal dan studi putusan; bahan analisis meliputi salinan putusan, KUHP, literatur fikih, dan kajian kontemporer yang dianalisis secara deskriptif-kualitatif dan komparatif. Hasil menunjukkan majelis secara formal menilai terpenuhinya unsur pembunuhan berencana sehingga vonis mengarah pada pidana mati menurut Pasal 340 KUHP. Secara tekstual unsur qishash terpenuhi dan keluarga korban tidak memberi pengampunan, namun kelemahan bukti forensik dan psikiatrik mengurangi kepastian faktual sebagai prasyarat penting menurut hukum pidana Islam sebelum menerapkan hukuman setimpal. Keywords: Death Penalty; Islamic Criminal Law; Murder of Parents; Proportionality; Rationality